DESIGN AND DEVELOPMENT OF EMPLOYEE ASSESSMENT APPLICATION PT. TASPEN (PERSERO) WEB-BASED - Muhammad Ayat Hidayat; Saepudin Nirwan (Jurusan Teknik Informatika dan Komputer, 2020)
All the time the survey procurement process is still rated less efficient because it still uses paper media. The impact, requires a longer cost and time. There are some employees who cheat by doing surveys more than one time. Beside that, HRD (Admin) in this case have difficulty in calculating the survey results in large numbers. Therefore, in final assignment , will be created a manager appraisal application system , thus creating harmonyfor each worker in it which will provide benefits to the institution, company, or hotel. This application is dedicated to employees. The application system will contain a questionnaire, where the contents of the questionnaire will contain some important things that will serve as guidelines for managers in improving performance based on the input of the employees themselves.